Service recovery through empowerment? HRM, employee performance and job satisfaction in hotels. (August 2019) - Hewagama, Gayani; Boxall, Peter; Cheung, Gordon; Hutchison, Ann
Highlights: Empowerment for service recovery in Sri Lankan hotels must be understood as multidimensional. Human resource management in these hotels fosters job competence to address service failures. Supervisors have greater job autonomy and impact and are rated more highly in service recovery. Empowerment in these hotels is hierarchical: it is carefully stage-managed and 'staircased'. Greater autonomy for service workers would help to enhance their job satisfaction. Abstract: This study tests the argument that human resource management in hotels enhances service-recovery performance and job satisfaction through empowering front-line employees to respond to service failures. After an initial phase of qualitative interviewing, dyadic data were gathered through a large-scale survey in thirty hotels in Sri Lanka. The results of structural equation modelling show that the HR practices and management styles adopted in this context help to develop job competence, which is then related to service-recovery performance and job satisfaction. However, they show that service recovery is carefully stage-managed and 'staircased' in this hotel context with empowerment strongly related to hierarchical level. Empowerment to address service failures is important in these hotels but it is deliberately graduated according to rank. While employee training shows benefits for both parties, greater job autonomy would enhance the well-being of these service workers.